Exploring the Nexus among Green Banking, Risk Management, and Profitability: Implications for Environmental Performance - Azad, Mohammad Abul Kalam; Islam, Md Aminul; Rahim, Hafizah Abdul; Ahsan, Mohammed Mahabubul; Imam, Hasina; Degago, Esayas; Molnar, Edina (Journal of Ecohumanism, 2025)
The financial system is now changing due to internal and external pressure of stakeholders towards environmentally responsible banking. The current study examined the nexus between green banking, risk management, and profitability on environmental performance for 2014-2023. The data was collected from the Fitch Solution databank in Malaysia using a non-probability purposive sampling method. The total observation was 210 of 21 samples. Prior to the regression analysis, this study conducted a diagnostic test. Hausman test was performed to select a model, either a fixed effect model or a random effect model. The findings revealed that liquidity, interest rate, and income diversification positively and significantly affect environmental performance. In contrast, the results showed that green banking (GBRNK) is the most integral factor when evaluating environmental performance. However, the results indicate that GBRNK significantly impacts environmental performance in the Bangladesh banking industry. Moreover, bank risks, such as credit and management efficiency, have a negative and significant relationship with environmental performance. On the contrary, profitability, such as ROA and ROE, has a positive and significant impact on environmental performance. These findings offer numerous insights into the banking strategy, regulatory policy, and future research directions to address the implementation of green banking practices. This study also verifies the use of institutional theory in the context of green banking.